UML-Based Design of a GIS-Based E-Commerce Application for MSMEs - John Friadi; Suroto Suroto; Alexsandri Sikumbang; Taufan Maulana Haries; Dodi Putra Yani (Jurnal Ilmu Siber dan Teknologi Digital, 2025)
Purpose: This study aims to design a Geographic Information System (GIS)-based e-commerce application for Micro, Small, And Medium Enterprises (MSMEs) using the Unified Modeling Language (UML). The novelty of this study lies in the integration of UML modeling with GIS-based features to support spatial visualization in MSME e-commerce systems, which is limited in prior studies. Methodology/approach: This research adopts a Research and Development (R&D) approach using the waterfall model, which was selected because of its suitability for structured system design with clearly defined requirements. Results/Findings: The results demonstrate that UML modeling, including use case, activity, and class diagrams, successfully represents system functionality, user interactions, and data structures in a systematic and consistent manner. The completeness and consistency of the model were evaluated based on the alignment between system requirements and diagram representation. However, this study is limited to system design without full implementation and empirical testing. Conclusions: This study introduces a GIS-based e-commerce design for MSMEs using UML modelling, a novel approach in integrating spatial features. The UML models effectively represent system functions and data. However, the study is limited by the lack of implementation and testing. Future research should focus on full implementation and empirical validation. Limitations: This study has limitations in that comprehensive system implementation and testing have not been conducted. Contributions: This research contributes conceptually and methodologically by providing a structured UML-based design model for GIS-integrated MSME e-commerce systems that can be used as a reference for future development and implementation.